Challenges in Eye-Gaze Interaction Systems: A Survey - Baharum A.; Ismail R.; Turumogan P.; Ismail I.; Noor N.A.M.; Deris F.D. (Institute of Electrical and Electronics Engineers Inc., 2025)
Eye-gaze, also referred to as eye tracking, enables users to control their computers or communication devices using their eyes as a mouse. Achieving accurate and precise eye-gaze positioning with low-cost devices is a crucial advancement in this field. This paper presents a survey of eye-gaze-based interaction systems, aiming to identify current techniques employed in this domain. Key issues related to eye-gaze-based interaction systems are discussed, along with the challenges they pose and potential future developments. Recent eye-gaze system review methods are also presented. Additionally, the paper provides a summary of research findings on eye-gaze methods, comparing the main phases of eye-gaze-based interaction. Over the past few years, researchers have proposed various methods and solutions to enhance the accuracy and performance of eye-gaze-based systems. These techniques find applications in diverse areas, such as virtual keyboard typing, immersive video technologies, virtual communication, assistive devices, screen control, effortless scrolling, and enriched reading experiences. Overall, eye-gaze-based interaction systems have the potential to enhance user-human experiences by identifying eye-gaze positions or points, thereby improving users' lifestyles and understanding of their machine. ? 2024 IEEE.